The Effect of Intrathecal Morphine Dose on Outcomes After Elective Cesarean Delivery: A Meta-Analysis. (July 2016) - Sultan, Pervez; Halpern, Stephen H.; Pushpanathan, Ellile; Patel, Selina; Carvalho, Brendan
Abstract : BACKGROUND: The intrathecal morphine dose achieving optimal analgesia for cesarean delivery while minimizing side effects has not yet been deduced. In this meta-analysis, our objective was to determine whether low- or high-dose intrathecal morphine provides acceptable duration and intensity of analgesia with fewer side effects. METHODS: A literature search (PubMed, EMBASE, MEDLINE, Scopus, Web of Science, and CINAHL) was performed to identify randomized controlled trials involving patients undergoing elective cesarean delivery under spinal anesthesia comparing low-dose (LD; 50–100 μg) morphine with higher dose (HD; >100–250 μg). The primary outcome was the time for first request for supplemental analgesia. The secondary outcomes included pain scores, morphine use, maternal side effects (vomiting and pruritus), and Apgar scores. Mean differences (MDs) and odds ratios (ORs) were calculated using random effects modeling with 95% confidence intervals (CIs). RESULTS: Eleven articles met our inclusion criteria. Four hundred eighty patients were recruited in all study groups (233 patients in the HD and 247 in the LD groups). The mean time to first analgesic request was longer (MD, 4.49 hours [95% CI, 1.85–7.13]; P = 0.0008) in the HD group compared with the LD group. Pain scores (0–100 scale) at 12 hours (MD, 2.54 [95% CI, −2.55 to 7.63]; P = 0.33) as well as morphine consumption at 24 hours (MD, 1.31 mg [95% CI, −3.06 to 7.31]; P = 0.42) were not significantly different. The incidence of nausea or vomiting (OR, 0.44 [95% CI, 0.27–0.73]; P = 0.002) and pruritus (OR, 0.34 [95% CI, 0.20–0.59]; P = 0.0001) was lower in the LD group. The incidence of Apgar scores <7 at 1 minute was not different between groups (OR, 1.11 [95% CI, 0.06–20.49]; P = 0.94). CONCLUSIONS: This meta-analysis shows that HDs of intrathecal morphine prolong analgesia after cesarean delivery compared with lower doses. The MD of 4.5 hours (95% CI, 1.9–7.1 and 99% CI, 1.0–8.2 hours) of pain relief must be balanced against the increased risk of maternal pruritus and vomiting. Results from this study can be used by clinicians to weigh the benefits and potential side effects of using HDs of intrathecal morphine for cesarean delivery. Abstract : Supplemental Digital Content is available in the text.Published ahead of print April 13, 2016